Two-Color Approach to Weekly Homework. Issue 2 (7th February 2019) - Klima, V.
Abstract: As teachers of mathematics we encourage our students to ask good questions, and we strive to help our students find and understand answers to these questions. This journey can be made more meaningful if students conclude by reflecting on their learning process. If we find careful questioning and reflection important, we should include such activities in our assessment. This article discusses two-color problem sets, in which students record what they do and what they do not understand about a problem, asking pointed questions about whatever is troubling them. In class, the students discuss their questions and use colored ink to record the answers they find. The article addresses assessment strategies for the two-color problem sets and student reactions to the assignments.